Environmental performances of the wastewater treatment plants: Green Index. (22nd June 2020) - Yapıcıoğlu, Pelin; Demir, Özlem
The Green Index as a new indicator to determine the environmental performance has been developed in order to reduce the unfavourable environmental impacts of the wastewater treatment plants. The main aim of this study is to reveal the environmental performances of the wastewater treatment plants. An industrial and a municipal wastewater treatment plant in Turkey have been compared in terms of the Green Index. The results revealed that in August, for the municipal and the industrial wastewater treatment plants, CO2 emission values were 0.972 and 0.42 kg/h, respectively. N2 O emissions were also 8.7 and 1.53 kg/h, respectively. CO2 emissions in September were with the values of 0.507 and 0.657 kg/h for the municipal and the industrial wastewater treatment plants, respectively and N2 O emissions were 5.4 and 1.2 kg/h, respectively. The Green Index of industrial wastewater treatment plant was lower than the municipal one with the values of 1.13 and 1.36, respectively.